2011
DOI: 10.14238/pi51.5.2011.266-71
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oral and intravenous cyclophosphamide in children with steroid-resistant nephrotic syndrome

Abstract: Background There are variations in remission rates following treatment of steroid-resistant nephrotic syndrome (SRNS) with cyclophosphamide.Objective To compare the efficacy of oral versus intravenous cyclophosphamide (CPA) in the management of pediatric SRNS.Methods This was a prospective study of 41 children with SRNS treated with CPA. One group received oral CPA at a dose of 2 mg/kg body weight/day for 8-12 weeks, while the other group received intravenous CPA at a dose of 500mg/m2 body surface area (BSA) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
(22 reference statements)
1
5
0
Order By: Relevance
“…This finding was similar enough with Hidayati et al that found average (SD) of ureum is 28.4 (21.5). 12 The highest creatinine levels in this study were 0.3-1.0 mg / dL, (71.7%), and had an average (SD) of 0.71 (1.02). For creatinine, Hidayati et al listed average and SD of 0.7 (0.7).…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…This finding was similar enough with Hidayati et al that found average (SD) of ureum is 28.4 (21.5). 12 The highest creatinine levels in this study were 0.3-1.0 mg / dL, (71.7%), and had an average (SD) of 0.71 (1.02). For creatinine, Hidayati et al listed average and SD of 0.7 (0.7).…”
Section: Discussionmentioning
confidence: 50%
“…For creatinine, Hidayati et al listed average and SD of 0.7 (0.7). 12 Whereas in the study of Narayan et al, the average creatinine was 0.92(0.25). 15 In children, the ratio of urine protein and creatinine or the ratio of albumin and creatinine to urine when it becomes very useful for diagnose and to rate the function of kidney because it is difficult to collect urine for 24 hours.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations